Reciprocal relations between students' academic enjoyment, boredom, and achievement over time. (April 2018) - Putwain, David W.; Becker, Sandra; Symes, Wendy; Pekrun, Reinhard
Abstract: The control-value theory (CVT) proposes that achievement emotions and academic achievement show reciprocal effects over time. Previous studies have examined how achievement emotions predict subsequent achievement. However, evidence is limited for whether achievement can also predict achievement emotions. To examine these reciprocal relations, data were collected about two achievement emotions: enjoyment and boredom, and mathematics achievement over four waves in a single school year in primary school students in Years 5 and 6. Results from structural equation modeling supported reciprocal relations between emotions and achievement. Higher enjoyment and lower boredom predicted greater subsequent achievement and, in turn, greater academic achievement predicted subsequent greater enjoyment and lower boredom. Furthermore, the relations between emotions over time were mediated by achievement. These findings build on the evidence base for CVT and further understanding of relations between achievement emotions and academic achievement in younger students. Highlights: Relations were examined between achievement and emotion in primary school children. Mathematics achievement positively predicted enjoyment and negatively predicted boredom. Enjoyment positively, and boredom negatively, predicted subsequent mathematics achievement. Emotions were mediated by mathematics achievement.